Advanced Dimensions of Serious Frauds in Corporate Governance: A Multidisciplinary Analysis - Panday, Kislay (Digital Repository of Theses, 2024)
Ensuring high-quality financial reporting is crucial to maintain stakeholder trust following major financial scandals. The fraudulent financial activities of a company can have substantial adverse effects on the overall economy, investors, workers, clients, and vendors. There has been a lot of debate in recent years about the methods that can be used to stop or expose unethical and opportunistic actions by companies. This study offers a thorough examination of corporate governance and its consequences for effectively combating fraud in organizational settings. The study highlights the crucial significance of corporate governance, which is confirmed by using Cronbach's Alpha to evaluate the reliability of survey instruments that measure different aspects related to governance awareness, types and causes of fraud, advanced fraud dimensions, governance effectiveness, technology integration, and recommendations for improvement. The internal consistency across these categories was thoroughly evaluated, revealing strong Cronbach's Alpha coefficients that indicate a high level of reliability and coherence among the survey items. The results confirm the dependability of assessments related to understanding of corporate governance, types of fraud, and proposals for reform. Additionally, the integration of technology and the efficacy of governance also exhibit appropriate levels of reliability. The results of this study establish a strong basis for comprehending the viewpoints of employees on governance processes and awareness of fraud. This will enable well-informed strategic choices to be made in order to improve the integrity, compliance, and resilience of the firm. Furthermore, the regression analysis demonstrates a significant correlation between corporate governance standards and instances of corporate fraud, suggesting that enhancements in governance are linked to reported reductions in fraud incidents. Corporate governance variables account for a significant proportion (40.2%) of the variation in fraud incidences, highlighting their crucial role in preventing fraud within firms. Future research should give priority to conducting longitudinal studies in order to evaluate the long-term effects of governance improvements on fraud prevention. Additionally, cross-industry analyses should be conducted to identify governance challenges that are specific to different sectors. Qualitative investigations should be carried out to examine the organizational contexts and stakeholder perceptions related to fraud prevention. Furthermore, research should explore the use of emerging technologies in governance and strategies for preventing fraud. Furthermore, by assessing the efficacy of training programs, analyzing the dynamics of global governance, and evaluating the impact of regulatory changes and environmental, social, and governance factors on governance frameworks, a deeper understanding can be gained. This understanding can then be used to mitigate fraud risks and promote ethical behavior in various organizational contexts. Researchers and professionals are urged to focus on filling in research gaps and promoting collaboration across different disciplines in order to enhance understanding, create strategies based on evidence, and contribute to the continuous improvement of effective governance frameworks and fraud management practices worldwide. This proactive strategy will help firms effectively navigate the intricacies of governance, improve transparency, and protect organizational integrity in a rapidly changing and linked business environment.